Say nothing a true story of murder and memory in Northern Ireland - Keefe, Patrick Radden 1976- (Doubleday, 2019)
""Meticulously reported, exquisitely written, and grippingly told, Say Nothing is a work of revelation." ...David Grann, #1 New York Times bestselling author of Killers of the Flower Moon From award-winning New Yorker staff writer Patrick Radden Keefe, a stunning, intricate narrative about a notorious killing in Northern Ireland and its devastating repercussions In December 1972, Jean McConville, a thirty-eight-year-old mother of ten, was dragged from her Belfast home by masked intruders, her children clinging to her legs. They never saw her again. Her abduction was one of the most notorious episodes of the vicious conflict known as The Troubles. Everyone in the neighborhood knew the I.R.A. was responsible. But in a climate of fear and paranoia, no one would speak of it. In 2003, five years after an accord brought an uneasy peace to Northern Ireland, a set of human bones was discovered on a beach.